Optimasi hidrolisis enzimatik pepton ikan pelagis kecil menggunakan pepsin dari lambung tuna (Thunnus albacares): Optimization of enzymatic hydrolysis of small pelagic fish peptone using pepsin from tuna (Thunnus albacares) stomach - Anabokay, Rolen Yaldivilmon; Nurhayati, Tati; Trilaksani, Wini (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
The abundant catch of small pelagic fish is often underutilized due to quality deterioration caused by mishandling, leading to economic and ecological losses. This study aims to find the best enzyme activity for breaking down fish meat and to describe the peptone that is wrapped in gum arabic and maltodextrin mixed in a 1:3 ratio. The peptone raw materials consist of mackerel (Rastrelliger sp.), yellowstripe scad (Selaroides sp.), and sardine (Sardinella fimbriata), as well as pepsin extracted from the stomach of yellowfin tuna (Thunnus albacares). A completely randomized design (CRD) was used, with a single factor consisting of three enzyme activity levels (3,000 U/mg, 6,000 U/mg, and 9,000 U/mg), conducted in two replications. The analysis results indicated that the total volatile base (TVB) value of the fish raw material reached 28.046 mg N/100 g, which remains within the acceptable consumption limit. The highest enzyme activity for breaking down substances was 3,000 U/mg, with an NTT/NTB value of 0.630±0.281a, and this was then used to make liquid peptone. The liquid peptone was encapsulated at a 1:3 (v/v) ratio using maltodextrin and gum arabic (1:3) as encapsulating agents. The peptone contained 35.86% protein, 1.5% ash, and 86.42% water solubility. Mixing liquid peptone with a 1:3 ratio created peptone that has 0.2% NaCl and a pH of 4.06, which is good for growing moderately acid-loving microbes. This study demonstrates that a 1:3 encapsulation ratio effectively produces stable, high-quality fish peptone, which shows potential for application as a microbial culture medium.